The Encyclopedic Dictionary “Russian Language” and the History of Its Publications in the Context of Philological Criticism (Филологический класс, 2021)
The purpose of the article is to analyze the new edition of the encyclopedia “The Russian Language” of the point of view of the traditional Russian lexicography and terminology. The article mentions the continuity of the compilation of dictionaries of linguistic concepts, starting with the first “Grammatical Dictionary” by N. N.Durnovo. It is noted that the book under analysis differs from the previous encyclopedias, typical by genre. Attention is drawn to the role of extralinguistic factors, and above all ideology, in the formation of the system of scientific views in the Soviet era. The achieve this goal, the following methods are used: historical-linguistic, comparative, contextual, method of critical analysis, sociolinguistic method. They allowed the author to identify and characterize the most informative and valuable dictionary entries, compare them with previous editions of the encyclopedia “The Russian Language”, point out the strengths and weaknesses in the preparation of terminological material, note the urgency of new approaches in the lexicographic description of the language system. The article dwells on the concepts of the encyclopedia and the dictionary in detail. said the author speaks about the innovative nature of some elements of the book. It is stressed that the updated image of the language in the linguistic terminology and discourse of philological science of the 21st century was presented at the right time. Emphasis is placed on the unconventionality of the entires on the history of the Russian language and the depth of analytical description of parts of speech and grammatical categories in diachrony. Considerable attention is paid to the critical assessment of essays on the personalities of Russian linguists. The author of the article criticizes the inconsistency of the editorial choice of surnames, the lack of completeness of the entries and insufficient bibliographic support. The author points out obvious omissions of well-known names and inaccuracies in the description. The author argues that the concept of a terminological dictionary is anthropocentric, and that the dictionary is an independent object of research from the point of view of philological criticism of scientific knowledge. The author suggests concrete ideas to improve the structure and content of the publication. The urgency of the encyclopedia for the study and generalization of information about the metalanguage of science is emphasized. The results of the analysis can be used in the theory and practice of lexicography, in terminology, in the theory of methods of language teaching as a system of concepts that forms the philologist’s worldview.